THE HISTORY AND CURRENT STATE OF THE OLYMPIC GAMES - Isoqobulov Rajabboy (Journals Park Publishing, 2022)
In this article, you will get a broad understanding of the history and current state of the Olympic Games. In addition, you can get information about some interesting sports and famous athletes of Uzbekistan and their achievements. The Olympic Games are one of the most important international sports gatherings that unite all people through sports. The Games are held every 4 years and are a huge event for all of humanity.
Keywords: Olympic Games, sport, IOC, Olympic Charter